2019
DOI: 10.1177/0954008319882757
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on compression property of multiaxial warp-knitted composites

Abstract: The wind turbine blades are exposed to various environments all the year round, especially temperature variations during the four seasons. To study the influences of temperatures on the mechanical properties of composite materials, the compression property in the 0°, 45°, and 90° directions of the multiaxial (triaxial and quadaxial) glass fiber warp-knitted composites at −30°C, 0°C, 20°C, and 40°C was analyzed, respectively. The stress–strain curves, strength, modulus, failure strain, and the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…As the key part of fabric composites, the fabrics are usually composed of different kinds of high performance fibers such as PTFE (self-lubricating function) and Nomex (reinforcing function), which together with the resin polymer enable fabric composites the characteristics of designability, high specific strength, fatigue resistance and light weight [6][7][8][9]. For the fabric weaving, parameters such as thickness, layer numbers and yarn types is correlated with the weave structure, thus influence the wettability property, adhesion property, wear debris capturing ability and load-carrying ability of the composites [10][11][12][13]. Based on that, to study the effect of fabric structure on the tribological property of warp-knitted fabric composites, it is significantly important to carry out the preparation process and tribo-tests for the warp-knitted fabric composites.…”
Section: Introductionmentioning
confidence: 99%
“…As the key part of fabric composites, the fabrics are usually composed of different kinds of high performance fibers such as PTFE (self-lubricating function) and Nomex (reinforcing function), which together with the resin polymer enable fabric composites the characteristics of designability, high specific strength, fatigue resistance and light weight [6][7][8][9]. For the fabric weaving, parameters such as thickness, layer numbers and yarn types is correlated with the weave structure, thus influence the wettability property, adhesion property, wear debris capturing ability and load-carrying ability of the composites [10][11][12][13]. Based on that, to study the effect of fabric structure on the tribological property of warp-knitted fabric composites, it is significantly important to carry out the preparation process and tribo-tests for the warp-knitted fabric composites.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the bending properties have been decreased significantly with the increase in temperature. Yang et al 19 investigated the influence of temperatures on the compression property of MWC. The results indicated that the compression performance has been decreased with the increase in temperature.…”
Section: Introductionmentioning
confidence: 99%